Council of Experts: chronic shoulder pain as a multidisciplinary problem - A. E. Karateev; A. M. Lila; N. V. Zagorodniy; L. I. Alekseeva; S. V. Arkhipov; V. V. Arkov; M. S. Makarov; A. P. Rachin; V. A. Shirokov; M. N. Khokhlova; V. A. Nesterenko (Современная ревматология)
Chronic shoulder pain (CSP) is a clinical syndrome associated with inflammatory and degenerative musculoskeletal changes, characterized by pain in the shoulder that persists for at least 3 months, arising or aggravated by functional activity in this area. The frequency of CSP in the modern population reaches 20–33%, it is one of the leading causes of severe suffering, disability and seeking for medical attention. The main causes of CSP are shoulder rotator impingement syndrome (subacromial impingement syndrome), calcific tendinitis, adhesive capsulitis, shoulder and acromioclavicular joint osteoarthritis. Accurate diagnosis of these diseases is necessary for the correct choice of treatment. Differential diagnosis is carried out using tests that evaluate the function of the shoulder joint and the rotator cuff muscles (Neer, Speed, Hawkins tests, etc.), as well as using instrumental methods (ultrasound, magnetic resonance tomography, X-ray). In CSP, it is necessary to exclude septic, oncological, visceral, systemic rheumatic and other diseases, as well as musculoskeletal pathology of the cervical spine, upper chest and back, which can cause pain in the shoulder region.Therapy for diseases that cause CSP should be personalized and complex, aimed at maximum pain control and restoration of function. For this purpose, non-steroidal anti-inflammatory drugs, local injection therapy with glucocorticoids, hyaluronic acid, and platelet-rich plasma are used. In some cases, muscle relaxants, antidepressants, anticonvulsants, local injections of botulinum toxin type A are indicated. Physiotherapy and medical rehabilitation methods play a fundamental role in the treatment of CSP.